Report of a patient with developmental delay, hearing loss, growth retardation, and cleft lip and palate and a deletion of 7q34‐36.1: Review of distal 7q deletions. Issue 7 (21st May 2013) - Rush, Eric T.; Stevens, Jadd M.; Sanger, Warren G.; Olney, Ann H.
Abstract The use of aCGH has improved our ability to find subtle cytogenetic abnormalities as well as to find more precise information in patients with previously known abnormalities. In addition, it has allowed more specific genotype–phenotype correlation. In this report we describe a patient with a chromosomal deletion initially diagnosed with conventional cytogenetic analysis which was redemonstrated and more specifically described upon aCGH analysis. Our patient is a 12‐year‐old female born to a 26‐year‐old G1P0 mother. She was noted as a neonate to have a bilateral cleft lip and cleft palate, abnormal external ears, dysmorphic facies, and moderate to severe hearing loss. She has subsequently shown developmental delay, hyperreflexia, seizures, hyperactivity, and absence of speech. Chromosomal analysis showed deletion of 7q34q36.1. FISH studies confirmed the deletion was interstitial. Parental chromosomes were performed and did not show any cytogenetic abnormalities. aCGH was recently performed for the patient to further characterize the breakpoints of the deletion and confirmed the deletion was interstitial and of 13.2 Mb in size. Both proximal and terminal 7q deletion show a different phenotype than that of our patient. A number of patients with similar deletions have been found and while significant variability is observed, a number of findings appear to be common to deletions in this region. Therefore, we feel that distal interstitial deletions of chromosome 7q represent a recognizable phenotype and could be considered a separate deletion syndrome. © 2013 Wiley Periodicals, Inc.